Determinants of Business Capital Application Services: Empirical Study from PT. Permodalan Nasional Madani, Indonesia - Mariam, Siti; Yolanna, Yolla; Sutawidjaya, Ahmad Hidayat; Rojuaniah (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to analyze the influence of security assurance, service quality, and corporate image on customer satisfaction and loyalty at PT Permodalan Nasional Madani, an entity supporting Micro, Small, Medium Enterprises, and Cooperatives (MSMEs) in Indonesia. Employing an associative design and quantitative approach through an online questionnaire, this research collected data from PT Permodalan Nasional Madani customers at the Ciputat Timur branch in South Tangerang. Data analysis was conducted using Structural Equation Modeling Partial Least Square (SEM-PLS) with SmartPLS software. The results indicate that service quality and corporate image have a positive impact on customer satisfaction and loyalty, while security assurance has not shown a significant influence. These findings underscore the importance of service quality and corporate image in fostering customer satisfaction and loyalty, while also identifying areas needing improvement to strengthen customer relationships.